Magnesium-manganese oxides for high temperature thermochemical energy storage. (February 2019) - Randhir, Kelvin; King, Keith; Rhodes, Nathan; Li, Like; Hahn, David; Mei, Renwei; AuYeung, Nicholas; Klausner, James
Highlights: MgO-MnO based redox thermochemical energy storage material with energy density greater than 1600 MJ m −3 . High exergy due to heat discharge at temperature greater than 1000 °C. Thermal storage efficiency greater than 85%. Acid solution calorimetry and drop calorimetry used to measure energy density. Material reactivity does not degrade over multiple thermochemical cycling. Abstract: The reactive stability and energy density of magnesium-manganese oxides for high-temperature thermochemical energy storage have been investigated. Three variations of material with molar ratios of manganese to magnesium of 2/3, 1/1, and 2/1 were prepared using solid-state reaction synthesis and were tested for thermochemical reactive stability and energy storage capability. Results show that oxygen released and absorbed (standard cm 3 g −1 ) by the materials remains unchanged over 20 cycles when cycled between 1200 and 1500 °C under an oxygen partial pressure (PO2 ) of 0.2 atm, indicating excellent reactive stability at high temperatures. Additional confirmation of reactive stability was obtained through testing over 10 energy storage cycles between 1000 and 1500 °C. The energy density of the material between 1000 and 1500 °C was determined through a combination of acid-solution calorimetry and drop calorimetry. The total volumetric energy densities (chemical, phase change, and sensible) obtained for samples of Mn/Mg of 2/3, 1/1, and 2/1 cycled between 1000 and 1500 °C are 1596, 1626 and 1654 MJ m -3, respectively.